Validity and Reliability Ethics of Performance Assessment in Epistemic Biology (EPAEB) Using Rasch Model - Manahan, Daniel; Wulan, Ana Ratna; Amprasto, Amprasto (Jurnal Pendidikan MIPA, 2024)
In this study, an instrument was developed that maps the degree of implementation of assessment ethics in performance assessment of students' epistemic understanding, specifically in biology. The study started with a literature review to find ethical violations in performing evaluations of learning biology science process activities. It included a review of the PISA 2025 framework on epistemic learning, which informed our development of the Ethics of Performance Assessment in Epistemic Biology (EPAEB) instrument. An Rasch analysis was performed to check the validity and the reliability of the instrument, which was distributed to 38 students from Bandung and Cimahi in Indonesia. The EAPEB measurement demonstrated fair validity and reliability based on the Rasch model. One fit analysis of items for relevance to explore validity, indicated four E58, D45, D50, D44 did not fit in the defined ranges and needed modification to enhance clarity. A person reliability value of 0.90 and item reliability of 0.92 indicate that the developed instrument has sufficient reliability for quantitative research.         Keywords: epistemic biology learning, performance assessment, assessment ethics.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1870-1879